Pengaruh Persepsi Mahasiswa Mengenai Lingkungan Kerja dan Gaji terhadap Minat Mahasiswa menjadi Internal Auditor - Aisha, Dinda (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
For accounting students, choosing a career represented the initial step in shaping their desired professional path. In the working world, graduates of accounting face various realities when making their career choices. After successfully completing their undergraduate education in the field of accounting, graduates have an array of career options to consider, one of which is becoming an internal auditor. Identifying competent and talented internal auditors remains a significant challenge. Therefore, it was essential to comprehend the factors that could influence a company's ability to attract potential candidates interested in internal auditor positions. The objective of this research was to investigate the impact of the work environment and salary on accounting students' interest in becoming internal auditors. Convenience sampling was the sampling method employed. The study included a sample of 70 accounting students from UNPAR. The research findings revealed that both the work environment and salary had an influence on accounting students' career choices to become internal auditors.